2020
DOI: 10.1007/s10584-020-02782-7
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of uncertainties in projecting future changes to extreme storm surge height depending on future SST and greenhouse gas concentration scenarios

Abstract: We assess uncertainties in projecting future changes in extreme storm surge height (SSH) based on typhoon data extracted from ensemble experiment results with four sea surface temperature (SST) conditions and three global warming scenarios using a single atmospheric global climate model. In particular, this study focus on typhoons passing around the Korean Peninsula (KP) defined as the region of 32 to 40° N and 122 to 132° E. It is predicted the number of the typhoons affecting the KP will decrease by 4~73% wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Hereby, the literature so far has mainly focused on deriving STC tracks and corresponding wind and pressure fields. Some work has been done exploring the effect of using these to derive offshore extremes for storm surge and wave heights compared to considering HTCs only (e.g., Meza-Padilla et al, 2015;Appendini et al, 2017) but with focus on different regions than the BoB (e.g., Australia -Haigh et al, 2014;Mexico -Meza-Padilla et al, 2015;northern Pacific Ocean -Mori and Takemi, 2016;Yang et al, 2020; or the USA - Lin et al, 2012;Appendini et al, 2017;Marsooli et al, 2019) or without taking waves into account, which is found to be an important factor leading to flooding in the northern BoB (Krien et al, 2017) and arguably worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Hereby, the literature so far has mainly focused on deriving STC tracks and corresponding wind and pressure fields. Some work has been done exploring the effect of using these to derive offshore extremes for storm surge and wave heights compared to considering HTCs only (e.g., Meza-Padilla et al, 2015;Appendini et al, 2017) but with focus on different regions than the BoB (e.g., Australia -Haigh et al, 2014;Mexico -Meza-Padilla et al, 2015;northern Pacific Ocean -Mori and Takemi, 2016;Yang et al, 2020; or the USA - Lin et al, 2012;Appendini et al, 2017;Marsooli et al, 2019) or without taking waves into account, which is found to be an important factor leading to flooding in the northern BoB (Krien et al, 2017) and arguably worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…-The impacts of uncertain parameters on real-time forecasting (e.g., Bastidas et al, 2016), including the wind field, model resolution, and input parameters. -The effect of uncertainty on the future projection of TC-generated waves and surges, including GCM physics, the spatial pattern of SST, and global warming scenarios (Yang et al, 2020). Considering the first approach, Lin and Chavas (2012) stated that the wind parameters are more effective on the surge height, in comparison with the sea surface drag.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the CMIP5 worst scenario (i.e., RCP 8.5) lead to higher surge height, with the largest range of uncertainty. Yang et al (2020) estimated the uncertainties of future projection of the potential extreme surge height under the effect of future SST conditions and global warming scenarios. Murakami et al (2013) examined the effect of physics and SST change patterns on the variation of TC frequencies.…”
Section: Introductionmentioning
confidence: 99%